Plant flowering mirrored in airborne pollen seasons? Evidence from phenological observations in 14 woody taxa. (1st November 2020) - Damialis, Athanasios; Charalampopoulos, Athanasios; Lazarina, Maria; Diamanti, Eleni; Almpanidou, Vasiliki; Maraidoni, Afroditi Maria; Symeonidou, Aliki; Staikidou, Evgenia; Syropoulou, Eleana; Leontidou, Kleopatra; Tsiripidis, Ioannis; Halley, John M.; et al.
Abstract: Flowering and pollen seasons are sensitive to environmental variability and are considered climate change indicators. However, it has not been concluded to what extent flowering phenology is indeed reflected in airborne pollen season locally. The aim of this study was to investigate, for a wide spectrum of plant species, the responsiveness of flowering to different environmental regimes and also to check for commensurate changes in the respective pollen seasons. Fourteen taxa were selected representing the families of Corylaceae, Cupressaceae, Fagaceae, Oleaceae, Pinaceae and Platanaceae. Each was studied for at least one full flowering year and in at least two sampling stations differing in elevation or direction within the period 2004–2011. Flowering observations were made 2–3 times a week, from flower differentiation to flower desiccation; >1000 daily observations were made in 225 plant individuals, in total. Data were regressed against meteorological parameters in an attempt to identify the driving factors of flowering onset and offset. Flowering dates were compared with dates of the related airborne pollen seasons per taxon; airborne pollen monitoring took place daily using a Hirst-type volumetric sampler. For all taxa, flowering started earlier at lower elevations or southern direction. Cumulative temperature proved to be the factor most significantly affecting flowering onset and end for all species ( p <0.001, R 2 >0.70). For the majority of the taxa examined, airborne pollen season did not coincide locally with the respective flowering periods of the selected species: flowering could precede pollen season, even for more than one month (as in C. avellana ), or start after the pollen season onset (as in P. brutia ). The strong sensitivity of flowering to air temperature is not the case in the respective pollen seasons. This raises questions on the relationship between flowering times and airborne pollen seasons and on the rather underestimated role of long-distance transport of pollen. Graphical abstract: Image 1 Highlights: Flowering and airborne pollen abundances were studied for 14 woody taxa. Flowering phenology was examined in differing elevations and directions. Flowering occurred earlier in 10 species at lower elevations or south directions. Flowering mismatch with pollen season indicated long-distance pollen transport. Cumulative temperature was an essential driver of flowering.